1995
DOI: 10.1080/01616412.1995.11740333
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism research of cryoanalgesia

Abstract: The sciatic nerves of rabbits were frozen at different temperatures (-20 degrees C, -60 degrees C, -100 degrees C, -140 degrees C, and -180 degrees C). The morphology and function of the frozen nerves were examined with light microscopy (hematoxylin and eosinophilin stain and a histochemical thiocholine method) and electron microscopy. The function of the nerve after freezing was assessed using short latency somatosensory evoked potentials, sensory conduction velocity, and electromyogram at various intervals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 0 publications
0
50
0
1
Order By: Relevance
“…Histological studies have shown that for treatment of nerves with temperatures from -20° to -60°C Wallerian degeneration occurs while leaving the endoneurium intact [53]. Additionally, a comparative study between crush lesion (a common model of Wallerian degeneration) and cryoneuromodulation treatment on a rat sciatic nerve showed comparable histological results of second degree injury [54].…”
Section: Cryoneuromodulationmentioning
confidence: 99%
“…Histological studies have shown that for treatment of nerves with temperatures from -20° to -60°C Wallerian degeneration occurs while leaving the endoneurium intact [53]. Additionally, a comparative study between crush lesion (a common model of Wallerian degeneration) and cryoneuromodulation treatment on a rat sciatic nerve showed comparable histological results of second degree injury [54].…”
Section: Cryoneuromodulationmentioning
confidence: 99%
“…published a 3-point nerve injury scale in 1943 [4], and in 1951, Sir Sydney Sunderland published a 5-point scale which gave more resolution to Seddon's scale (Table 1) [5]. These scales classify nerve injury as a function of temperature [6,7]:…”
Section: Nerve Anatomymentioning
confidence: 99%
“…Cryoneurolysis is the direct application of cold temperatures, resulting in a second-degree injury to the peripheral sensory nerve [7]. Treatment in this temperature range causes a reversible degeneration of the axon beginning at the site of treatment and proceeding distally [8].…”
Section: Cryoneurolysis Wallerian Degeneration and Nerve Regenerationmentioning
confidence: 99%
See 2 more Smart Citations